Risk factor analysis stress in retirement - Alam Yusuf, Bahrul; Laely Ramadani, Meida (Proceedings Series on Health & Medical Sciences, 2020)
Stress is the reaction of the body to circumstances which cause pressure, shift, emotional distress, it can cause stress in the elderly who have retired. The aim of the research was find the factors that cause stress in retired elderly people. This research was used methods of qualitative research with a descriptive approach. Samples were collected in the Bangbayang Village Government Area through snowball sampling of as many as 7 (seven) elderly retirees. The results of this study indicate that of the elderly with ages of 60 years up to 2 people, 63 years up to 1 person, 66 years up to 1 person, 1 person 70 years old, 1 person 74 years old and 1 person 75 years old. There are five factors that cause stress in older retirees, such as: factors of social support, factors of economic status, current employment factors, factors of self-acceptance, and factors of life independence. Of the five stress-causing causes, 3 main factors faced by certain elderly pensioners are related to aspects of social care, economic stability, current employment.